A case of the world's largest renal cell carcinoma. Issue 1 (25th October 2020) - Takeda, Kotaro; Murray, Gina; Vohra, Nasreen; Fallon, John T
Abstract : Introduction: Renal cell carcinoma is often discovered at an early stage due to the increased use of imaging studies in the current era; therefore, its presentation as a gigantic renal cell carcinoma is rarely encountered. Case presentation: A 59‐year‐old male presented to our hospital due to dizziness, fatigue, and increasing abdominal distension. A computed tomography scan showed an extremely large mass occupying most of the abdomen and pelvis. Surgical resection of the mass was performed. The largely cavitary mass with fibrous capsule was 43 cm and 13.0 kg, and contained a large amount of necrotic tissue. A portion of the left kidney was identified at the periphery of the mass, indicating that the tumor was arising from the left kidney. The final pathologic diagnosis was type 1 papillary renal cell carcinoma. Conclusion: To the best of our knowledge, this tumor is the world's largest malignant renal tumor.